السلوك النمطي لدى أطفال التوحد من وجهة نظر المربيات - بورقعة, مروة; قدادرة, شوقي (جامعة الوادي - University of Eloued, 2023)
تعالج الدراسة الحالية موضوع السلوك النمطي لدى أطفال التوحد من وجهة نظر المربيات، حيث اعتمدت هذه الدراسة على المنهج الوصفي الاستكشافي، وذلك باستخدام مقياس السلوك النمطي لطفل طيف التوحد من وجهة نظر المربيات، والذي تم التأكد من خصائصه السيكومترية (الصدق-الثبات) على عينة قوامها 39 فردا. تم تطبيق أدوات الدراسة على العينة التي تم اختيارها بطريقة قصدية، بجمعية السعادة والمركز البيداغوجي بالدبيلة بولاية الوادي. ومن خلال النتائج التي تم التوصل إليها دلّت على أن مستوى شدة السلوك لدى الأفراد عينة أطفال التوحد من وجهة نظر المربيات كان ضعيف أما بالنسبة لمستوى متوسط التكرار السلوك النمطي لدى عينة الدراسة. Abstract: The current study deals with the issue of stereotypical behavior among children with autism from the educators' point of view (exploratory study) in the province of El Oued. This study relied on the exploratory descriptive approach, using the standard behavior scale for the autism spectrum of the child from the educators' point of view, whose psychometric properties (honesty-stability) were confirmed on a sample of 39 individuals. The study tools were applied to the sample that was chosen in an intentional way, at the Saada Association and the Pedagogical Center in Débila, in the province of El Oued. The results indicated that the level of severity of behavior among individuals in the sample of autistic children from the educators' point of view was weak, as for the average level of repetition of typical behavior in the study sample.
دراسة استكشافية بولاية الوادي
مقال
Keywords: السلوك النمطي ; التوحد; stereotyped behavior - autism